A STUDY ON THE BODY PERCEPTION IN PHYSICAL EXERCISES PRACTICING IN THE GYMS OF CONSTANTINA – RS (Fiep Bulletin - online, 2016)
The purpose of this study was to verify the conceptions of individuals about their body image, and their satisfaction with their own bodies. The perception of body image was identified by means of the protocol of the silhouettes of Stunkard. We interviewed fourty one individuals of both sexes, with ages between fourteen and fifty-six years old all regular visitors of the Gyms in the city of Constantina - RS. It also was performed a bibliographic review in order to build basement history on the body. The participants in the research, although showing small image distortions, marking silhouettes close from its own, demonstrated a positive view on the body itself. According to the bibliographic review we realized that there is a great influence of society on the idealization of the body suitable for individuals at any historic time. It is concluded that the practice of physical exercises exert positive effect on the health and the positive view of their own body image, providing thus higher quality of life and well-being.
Keywords: Body Image. Perception. Body. Health. Aesthetics.